An application of the spatial regression model for analyzing tourism receipt growth of provinces/cities in Vietnam - Nguyễn Văn Sĩ; Nguyễn Viết Bằng (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2020)
The paper defines and measures key factors regarding to tourism receipt of provinces/cities in Vietnam through spatial regression model. This study has used qualitative and quantitative researches: (i) qualitative carried out through deep interview with 09 experts, and (ii) quantitative research conducted through spatial regression model with secondary data from 2013 to 2017 of Vietnam’s provinces/Cities. The result shows that: tourism receipt is directly affected by tourist arrivals, population, the volume of tourist movement. Moreover, the result of the study is empirical evidence that there is a correlation between neighboring provinces/cities in tourism receipt growth of provinces/cities, it means that tourism receipt growth of this province has an impact on tourism receipt growth of other neighboring provinces/cities. In addition, the result also shows that: tourist arrivals, population, and the volume of tourist movement have spatial interaction between neighboring provinces.